Overcoming Financial Sector Challenges through Value-Based Banking: A Study from Nepal’s Banking Sector - Jha, Anil Kumar (Journal of Economics and Management, 2025)
The Nepalese banking sector currently faces several challenges. These include worsening asset quality, increased pressure on capital adequacy, declining profitability, difficulties retaining employees, rising cybersecurity threats, a growing number of allegations against financial institutions, and inadequate corporate governance frameworks. In this situation, applying Value-Based Banking (VBB) appears to be a viable approach to promoting sustainable banking practices. VBB helps develop business models that meet the needs of both the real economy and the surrounding community. By connecting banking with the community, many challenges in the banking sector can be addressed. This study aims to look at how VBB principles can help tackle the issues in Nepal's banking sector. It also evaluates the performance of Nepalese commercial banks based on eight quantitative factors linked to value-based banking. Additionally, it examines the regulatory and supervisory actions taken by the Nepal Rastra Bank (NRB) to encourage these banking practices. The findings show various regulatory and supervisory measures that support adopting VBB in Nepal. The analysis further reveals that banks have different competitive advantages across the eight VBB criteria. Specifically, private banks have made more substantial investments in triple bottom line assets than government banks, which tend to struggle with asset quality. Different banks rank as top performers based on the eight criteria of VBB in Nepal. In conclusion, the principles of VBB have considerable potential to address the ongoing challenges in the Nepalese banking sector. Integrating these principles may also strengthen the connection between the banking sector and the community, promoting a shift toward more sustainable banking practices.